Phytochemical Screening and Cytotoxicity Test of Sidaguri Leaf (Sida rhombifolia Linn.) Fractionated Extract with Brine Shrimp Lethality Test (BSLT) Method - Lisnawati Tumanggor (Jurnal Ilmiah Berkala Sains dan Terapan Kimia, 2024)
Traditional medicine can be an alternative in the treatment of cancer. One of the traditional medicines used as herbal ingredients that has the potential to be anticancer is sidaguri ( Sida rhombifolia Linn.). The leaves of S. rhombifolia are plants belonging to the family Malvaceae . S. rhombifolia plants contain chemical compounds. This study aims to determine the chemical content of sidaguri extract and potential cytotoxicity based on LC50 (Lethal Concentration 50) values in the death of nauplii Artemia salina Leach after administration of ethanol extract and n-hexane fraction, ethyl acetate and water. The method used S. rhombifolia leaves that have been in the form of simplicia were extracted with 70% ethanol solvent using the ultrasonication method. Then tested for the content of chemical compounds. Phytochemical screening results showed that S. rhombifolia ethanol extract contained alkaloid compounds, flavonoids, saponins, tannins, and triterpenoids. The ethanol extract was further fractionated using the solvents n-hexane, ethyl acetate and water. The cytotoxicity of S. rhombifolia extract was tested using the Brine Shrimp Lethality Test (BSLT) method using ethanol extract, n-hexane fraction, ethyl acetate fraction and toxic water fraction against Artemia salina or less than 1000 ppm, of the four test extracts that had the smallest LC50 value was ethanol extract which was 320.15 μg / ml and a lkaloid compounds fractionated from ethanol extract of Sidaguri leaves Fraction n hexan 600.10 μg / ml, ethyl acetate 575.06 μg / ml and water 873.21 μg / ml results obtained that ethanol extract is more cytotoxic than fractionation.